Physical activity and diet among adolescents of Kathmandu, Nepal: Knowledge and attitudes - Pahlm, J; Svensson, J; Joshi, S K; Swahnberg, K (Journal of Kathmandu Medical College, 2014)
Background: Non-communicable diseases are becoming more prevalent in Nepal and many risk factors attributing to these diseases are behaviour-related and therefore preventable. Objective: The aim of this study was to investigate the attitudes among students of grade eight and nine in Kathmandu toward physical activity and diet and their knowledge about how it affects their health. Methods: We conducted four focus groups that included 24 students to explore knowledge and attitudes toward physical activity among them. Focus groups were recorded and transcribed verbatim later. Method described by K. Malterud, inspired by Giorgi’s phenomenological method was used to analyze the transcribed material. Results: Participants considered physical activity to be benefi cial for health in many ways. They also believed that healthy food is important to avoid diseases. Several participants mentioned that a balanced lifestyle is essential for a healthy life. Conclusion: Though the students saw the importance of physical activity and a healthy diet to avoid diseases and stay healthy, most of them did not connect a lack of physical activity and unhealthy diet to possible noncommunicable diseases in the future. DOI: http://dx.doi.org/10.3126/jkmc.v2i2.10623 Journal of Kathmandu Medical College, Vol. 2, No. 2, Issue 4, Apr.-Jun., 2013, Page: 51-58